2007
DOI: 10.1308/003588407x202038
|View full text |Cite
|
Sign up to set email alerts
|

Giant Haemangioma of the Liver: Is Enucleation Better than Resection?

Abstract: Ann R Coll Surg Engl 2007; 89: 490-493 490Haemangioma is the commonest benign liver tumour with an incidence of 0.4-7.3% in autopsy series. 1 With the increasing use of imaging modalities, asymptomatic giant haemangiomas (> 4 cm in size) are detected more frequently. These lesions can, at times, present a diagnostic dilemma. 2There is considerable controversy regarding the ideal treatment of giant haemangiomas of the liver. Some authors, on the basis of long-term follow-up of such lesions, propose that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Finally, 7 studies involving 913 patients were included in the meta-analysis. [9][10][11][12][13][14][15] All included studies were non-randomised controlled trials. Three were from the United States, one was from Turkey, one from India, one from Italy and one from China.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 7 studies involving 913 patients were included in the meta-analysis. [9][10][11][12][13][14][15] All included studies were non-randomised controlled trials. Three were from the United States, one was from Turkey, one from India, one from Italy and one from China.…”
Section: Resultsmentioning
confidence: 99%
“…Two common procedures for surgical intervention include enucleation and resection. Until recently, authors reported that enucleation was associated with decreased morbidity, intraoperative bleeding, hospital stay, and operative times [29][30][31][32]. Nevertheless, these studies included few patients with hemangiomas >10cm.…”
Section: Discussionmentioning
confidence: 99%
“…Enucleation was first described in 1988 [24], and since then, many researchers have reported their experiences with this technique [22,[25][26][27][28]. Many institutions reported that enucleation can be performed safely, even with total vascular occlusion, when the hemangioma is very large or at a dangerous anatomical location adjacent to the inferior vena cava or a major hepatic vein.…”
Section: Discussionmentioning
confidence: 99%